1991
DOI: 10.1111/j.1570-7458.1991.tb01451.x
|View full text |Cite
|
Sign up to set email alerts
|

Parasitization of granulosis‐virus infected and noninfected Agrotis segetum larvae and the virus transmission by three hymenopteran parasitoids

Abstract: Apanteles telengai Tobias, Aleiodes gasteratus (Jurine) and Campoletis annulata Tschek parasitized significantly more healthy than granulosis virus (GV)‐infected Agrotis segetum D. & Schiff. larvae. Females of the three parasitoid species that had oviposited previously in GV‐infected A. segetum larvae transmitted the virus to healthy A. segetum larvae in subsequent oviposition. A. telengai and A. gasteratus females also transmitted the GV on unsuccessful oviposition attempts. Male parasites did not transmit th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 10 publications
2
21
1
Order By: Relevance
“…Caballero et al (1991) reported that Apanteles telengai (Hymenoptera: Braconidae), Aleiodes gasteratus (Hymenoptera: Braconidae), and Campoletis annulata (Hymenoptera: Ichneumonidae) parasitized significantly more healthy than the granulovirus-infected larvae of Agrotis segetum (Lepidoptera: Noctuidae). Beegle and Oatman (1975) observed that female Hyposoter exiguae (Hymenoptera: Ichneumonidae) laid as many eggs in NPV-infected Trichoplusia ni (Lepidoptera: Noctuidae) larvae as in non-infected larvae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caballero et al (1991) reported that Apanteles telengai (Hymenoptera: Braconidae), Aleiodes gasteratus (Hymenoptera: Braconidae), and Campoletis annulata (Hymenoptera: Ichneumonidae) parasitized significantly more healthy than the granulovirus-infected larvae of Agrotis segetum (Lepidoptera: Noctuidae). Beegle and Oatman (1975) observed that female Hyposoter exiguae (Hymenoptera: Ichneumonidae) laid as many eggs in NPV-infected Trichoplusia ni (Lepidoptera: Noctuidae) larvae as in non-infected larvae.…”
Section: Discussionmentioning
confidence: 99%
“…The transmission of viruses by parasitoids can be categorized into two means: mechanical vectors in the translocation of viruses as a result of contaminated body parts contacting host food sources (Irabagon and Brooks, 1974;Beegle and Oatman, 1975;Raimo et al, 1977;Young and Yearian, 1990;Sait et al, 1996), and biological vectors in the translocation of viruses as a result of the direct inoculation of the host via a virus-contaminated ovipositor (Beegle and Oatman, 1975;Levin et al, 1983;Hamm et al, 1985;Caballero et al, 1991). In this study, we examined the possibility of M. pulchricornis wasps as mechanical and biological vectors of SpltNPV, but no parasitoid females transmitted an effective dose of SpltNPV to other hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, an earlier general conclusion among researchers that postponing the exposure of parasitized larvae to a host baculovirus increased the percentage of successful parasitoid development, may be a function of more than just enabling the parasitoid sufficient time to develop and emerge from infected tissue before imminent virus-induced host mortality (3, 5, 14, 30).As a baculoviral host infection can decrease the survival of a parasitoid, it is apparent that it would be in the parasitoid' s best interest to avoid infected hosts in the field. Research to date has shown that many, although not all, hymenopteran parasitoids are able to discriminate to varying degrees, between infected and non-infected hosts(8,16,17,35). For example, both Venturia canescens and Meteorus gyrator females were shown to reduce the number of eggs that they inserted into betabaculovirus-infected Indian meal moth, Plodia interpunctella and Lacanobia oleracea larvae, respectively, based on the level of the host=s infection(38,45).…”
mentioning
confidence: 97%
“…However, our field experiment was conducted at a high-virus concentration (1.6 × 10 8 OB·ml A 1), and whether host discrimination by M. pallidipes would be the same at a lower virus concentration remains to be determined. In addition, our results can be viewed in the context of the parasitoid-pathogen interspecific competition hypothesis (Caballero, Vargas-Osuna, & Santiago-Alvarez, 1991;Hochberg, 1991), which postulates that M. pallidipes and SlNPV would compete for the host resources in dually attacked hosts (infected and parasitized), with negative consequences to the reproduction of both parasitoid and virus, leading M. pallidipes to increase its fitness by avoiding parasitizing NPV-infected larvae.…”
mentioning
confidence: 92%